Effects of altitude, land use and microsites on early life performance of a high mountain tree: Insights from an in situ sowing experiment. Issue 10 (16th July 2019) - Cáceres, Yolanda; Schrieber, Karin; Lachmuth, Susanne; Auge, Harald; Argibay, Daihana; Renison, Daniel; Hensen, Isabell
Abstract: Aim: Understanding the forces that drive range shifts in forest landscapes is imperative for predicting species distributions under anthropogenic climate and land use change. However, empirical studies exploring how these components jointly influence critical early life stages of mountain tree species across environmental gradients are scarce. We used the high mountain tree Polylepis australis as model species to investigate the relative importance of altitude and associated climatic conditions, land use for livestock and microsite characteristics on early life performance. Location: Córdoba Sierras, central Argentina. Methods: We set up an extensive in situ sowing experiment with a robust split‐plot design that integrated spatial scales ranging from 0.4 m 2 subplots at the microsite level (associated with vegetative and microtopographic structures), to livestock exclosure and enclosure plots of several hectares, to an altitudinal gradient of 1, 000 m. Components of early life performance were monitored across two subsequent growing seasons. Results: Microsite characteristics played a fundamental role in P. australis establishment, whereby interactions with altitude and/or land use suggested alternate mechanisms: facilitation (likely reduced desiccation) dominated at low altitude while at high altitude, abiotic stress (likely intensive frost and radiation) overruled any microsite effects. At mid‐altitude, benefits of competition release prevailed over facilitation and microsite effects gained importance under livestock presence. Inconsistencies between pre‐ and post‐emergence responses illustrated potential trade‐offs between beneficial and detrimental effects of microsite conditions upon performance throughout early life: a favourable location for seeds may abruptly turn adverse for seedlings. Main conclusions: We unravel how changes in altitude, anthropogenic disturbances and microsite characteristics jointly modulate P. australis performance across stages of early establishment. Such information is fundamental when categorizing specific microhabitats as "safe sites" for tree regeneration especially in mountain environments with high spatio‐temporal heterogeneity.